Employee Performance: Work Ability and Work Motivation - Iin Emy Prastiwi; Sri Laksmi Pardanawati; Deni Kurniawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to determine the factors that affect employee performance at Bank BTN Syariah KCS Solo. The independent variables in this study were work ability and work motivation. The population in this study were 40 employees of Bank BTN Syariah KCS Solo. All populations were sampled in this study. This research shows that work ability does not have a significant effect on employee performance, while work motivation has a significant positive effect on employee performance. Bank BTN Syariah Kcs Solo should improve employee performance by providing motivation with various innovations, for example motivational briefings on the sidelines of working hours, inviting motivators and so on to keep employee motivation high. Keyword: Employee Performance, Work Ability, Work Motivation